An Inquiry in the Exploration of Persian and âArabic Literature Connection (The Case of âIrony in Masnavi Maânavi and Arabic âLiterature)â - وحید سبزیان پور; صدیقه رضایی; سمیره خسروی (مطالعات زبانی و بلاغی)
Molana has used expressive and rhetorical figures of âspeech in his artistic pictures of Masnavi Maânavi. Irony as a âvery useful means has attracted the attention of Molana as âsuch that he has declared most of his speech in the form of âthis method. In this research, irony and its pictorial function âhave been investigated with the analytic-descriptive method. âWe made an attempt to investigate the relationship between âMasnaviâs ironies and defined Arabic ironies as well as to âfind the similarities of this issue in mAsnavi and Arabic âLiterature. The result of the study shows that ironies in âMasnavi have similarities with Arabic irony and as each âculture has its own specific irony so this commonality shows âthe deep historical and cultural connection of these two âLiteratures: Arabic and Persian. Other evidences depict that at âleast eight of the ironies mentioned in this article are Iranian. âIn contrast to general insights, we canât claim that the rest of âironies are Arabic.â